Exploring 2D/3D input techniques for medical image analysis - Zudilova-Seinstra, Elena V. (2013)
We describe a series of experiments that compared the 2D and 3D input methods for selection and positioning tasks related to medical image analysis. For this study, we chose a switchable P5 glove controller, which can be used to provide both 2DOF and 6DOF input control. Our results suggest that for both tasks the overall completion time and accuracy can be improved when the input device with more degrees of freedom is used for manipulation of the visualized medical data. However, 3D input appeared to be more beneficial for the positioning task than for the selection task.